Deixis Found in King Charles III's Speech from the Throne (2025) - Arya Hardi Winata; Khairil Akbar; Leo Anggara; Muhammad Daffa Aqilah (Journal of Applied Linguistics, 2026)
This study examines the use of deixis in King Charles III's Speech from the Throne (2025) by applying Yule’s (1996) framework, which categorizes deixis into person, spatial, and temporal types. Using a qualitative descriptive approach, the analysis focuses on the official transcript published on the Government of Canada’s website. The data were categorized and analyzed to determine the frequency and purpose of each deictic category within the speech. A total of 127 deictic expressions were found, consisting of 66 person deixis (51.97%), 55 spatial deixis (43.31%), and 6 temporal deixis (4.72%). Person deixis, particularly pronouns such as I, we, our, and you, is the most dominant and serves to build solidarity and shared identity between the King and his audience. Spatial deixis, including here, there, this, and that, reinforces unity by referring to physical and symbolic aspects of the nation. Although temporal deixis appears infrequently, it connects the present moment with Canada’s historical continuity and future aspirations. Overall, deixis functions as a strategic linguistic tool that strengthens authority, unity, and national identity in royal political discourse. Keywords : Deixis; Political discourse; King Charles III's Speech; National identity